Efficacy and safety of glucocorticoid combined with cyclophosphamide therapy on membranous nephropathy: a systematic review and meta-analysis - Feng, Chengcheng; Chen, Xuexun; Wang, Xiangming; Guo, Min; Guo, Zhentao (Frontiers in Pharmacology, 2024)
Background This review systematically evaluates the efficacy and safety of the combined treatment of glucocorticoids (GC) and cyclophosphamide (CTX) in patients with membranous nephropathy (MN).As of June 2024, a comprehensive literature search was performed utilizing several reputable databases, including PubMed, Embase, the Cochrane Library, China National Knowledge Infrastructure (CNKI), and Wanfang. A meta-analysis was then carried out using Review Manager 5.4 and STATA/SE-15 software. Registration number: CRD42024566477.This research evaluated a total of 22 articles involving 1,971 patients. The findings revealed that patients with MN receiving combined GC and CTX therapy had significantly higher complete remission rates (odds ratio = 1.78, p = 0.02) and total remission rates (odds ratio = 2.14, p = 0.01) when the follow-up period exceeded 12 months. Additionally, this treatment demonstrated greater efficacy in lowering serum creatinine levels compared to the control group (standardized mean difference = -0.19, p = 0.04), while its relapse rate was also lower than that of the control group (odds ratio = 0.51, p = 0.009). However, it has a high incidence of serious adverse effects (odds ratio = 2.32, p = 0.03).Our systematic review highlights that the combination of GC and CTX demonstrates superior long-term effectiveness and reduced relapse rates in managing membranous nephropathy (MN). Furthermore, this drug combination is considered the optimal choice for normalizing serum creatinine levels. Data on the effectiveness and safety of glucocorticoids alone versus other drugs alone, and the treatment of secondary membranous nephropathy (SMN), are limited.